The efficacy and social validity of a group cognitive behavioural therapy for young migrants from war-affected countries - Ooi, Chew Sia (Curtin University, 2013)
School-based group intervention has been suggested to be an effective framework when working with war-affected children. However, many of the studies published in the literature are limited by small sample size, absence of randomisation, absence of a control group, unsatisfactory programme integrity procedure, and narrow study outcomes. One of the promising group interventions was the Teaching Recovery Techniques (TRT; Smith, Dyregrov, & Yule, 2000). It was developed based on the cognitive behavioural models of posttraumatic stress disorder (PTSD) and has demonstrated preliminary efficacy in reducing PTSD and associated symptoms in refugee children in developing countries (Barron, Abdallah, & Patrick, 2012) and developed countries (Ehntholt, Smith, & Yule, 2005). However, the efficacy of this intervention has not been tested in an Australian context. The aim of this research was to examine the efficacy of the TRT in improving the emotional and behavioural outcomes of war-affected children resettled in Australia using a cluster randomised controlled trial (RCT) with pretest, posttest, and 3-month follow-up design. The secondary aim of the research was to examine the social validity of the intervention.These aims were investigated utilising quantitative and qualitative methods in three studies. Study One involved a pilot study which was conducted with a sample of four participants prior to the RCT in order to investigate the feasibility of the research. Feedback from students and parents suggested the appropriateness of the intervention and research procedure. In Study Two, a cluster RCT involving 82 participants (aged 10 to 17 years) was conducted. Participants were randomised by school into the 8-week intervention (n = 45) or the waiting list (WL) control condition (n = 37). Inclusion criteria were exposure to war or violence, being a recent arrival, and mild to moderate symptoms of PTSD. Exclusion criteria were meeting the clinical cut off score of PTSD, limited English proficiency, being an unaccompanied refugee, and currently receiving psychological treatment. Symptoms of PTSD, depression, and internalising and externalising problems were assessed using the Children Impact of Event Scale-13, Birleson Depression Self-Rating Scale, and Hopkins Symptom Checklist-37A respectively. Psychosocial functioning was measured using parent- and teacher-rated versions of the Strengths and Difficulties Questionnaire. It was hypothesised that participants in the intervention condition would experience greater symptom reductions, compared to participants in the WL condition.A medium intervention effect was found for depression symptoms. Participants in the intervention condition experienced a greater symptom reduction than participants in the WL condition, F(1,155) = 5.20, p = .024, partial η 2 = 0.07. This improvement was maintained at the 3-month follow-up, F(2,122) = 7.24, p = .001, partial η 2 = 0.20. There was a non-significant trend for a greater reduction of PTSD symptom in the intervention condition, F(1,154) = 3.09, p = .081, partial η 2 = 0.04. Changes in internalising problems, F(1,155) = 0.03, p = .871, partial η 2 = 0.00; externalising problems, F(1,155) = 0.25, p = .621, partial η 2 = 0.01; parent-rated total difficulties, F(1,133) = 0.28, p = .599, partial η 2 = 0.00; parent-rated prosocial behaviour F(1, 155) = 0.07, p = .798, partial η 2 = 0.00; teacher-rated total difficulties, F(1,145) = 0.52, p = .472, partial η 2 = 0.00; and teacher-rated prosocial behaviour, F(1, 145) = 0.03, p = .874, partial η 2 = 0.00, were not significant between the conditions. Analysis of reliable change revealed that there were more participants in the intervention condition than participants in the WL condition achieving reliable improvements in PTSD (21% vs. 11%) and depression (12% vs. 6%) symptoms.Study Three involved an investigation of the social validity of the intervention using a student-rated evaluation form and feedback interview with students and parents. Students described looking forward to the weekly sessions and identified a number of skills that were particularly helpful to them. Some parents reported that their children had not involved them in their learning process but were able to identify positive changes in the emotions and behaviours of their children. Also, parents considered the intervention as culturally sensitive and were supportive of their children receiving the intervention.Although this research has several limitations such as the absence of a placebo control group and blinding procedures, and small cluster sample size, the findings demonstrated that the group-based intervention is culturally sensitive and efficacious in reducing depression symptoms in war-affected young migrants. The broader implication of the results for practitioners is that this intervention can be xiii implemented as a time- and cost-effective early intervention programme for war affected children with depression symptoms.